Global partnerships in combating tropical diseases: assessing the impact of a U.S. withdrawal from the WHO - Ikponmwosa Jude Ogieuhi; Victor Oluwatomiwa Ajekiigbe; Stephen Olaide Aremu; Victory Okpujie; Peace Uchechi Bassey; Adetola Emmanuel Babalola; Pelumi Gbolagade-Jonathan; Chidera Stanley Anthony; Ifeoluwa Sandra Bakare (Tropical Medicine and Health)
Abstract Background Annually, tropical diseases are a major cause of mortality; for instance, in 2019, neglected tropical diseases (NTDs) caused 150,000 deaths and 19 million DALYs, with sub-Saharan Africa bearing over half the burden and the other concentrations in Asia and South America. Their impact, though significant, is lower than ischemic heart disease and respiratory infections. The World Health Organization is critical in combating these tropical diseases through surveillance, information campaigns and health promotion. Through international collaborations and initiatives, tropical diseases have been relatively mitigated; for example, global initiatives eradicated smallpox (1980), cut polio cases by 99% (1988–2022), and reduced Guinea worm cases from 3.5 million (1986) to 14 (2023), while NTD prevalence dropped significantly from 1990 to 2020. Main body The potential departure of a major player like the United States, the largest WHO donor, which contributed $1.284 billion (20% of its budget) in 2022–2023, surpassing the Gates Foundation ($689M), Gavi ($500M), and the EU ($412M), and its potential withdrawal threatens WHO’s financial stability, jeopardizing emergency responses, disease prevention, and global health initiatives, urging stakeholders to reinforce global health systems. Governments, international organizations, and private partners must work together to create strong, flexible frameworks that prioritize prevention, research, and equitable healthcare delivery. By fostering collaboration, transparency, and mutual accountability, the global health community can continue to make progress toward eliminating the burden of major tropical diseases such as malaria and Dengue fever, among others. Failure to do so could reverse hard-won gains such as the 99% reduction in polio cases since 1988, the near-eradication of Guinea worm disease (from 3.5 million cases in 1986 to 14 in 2023), and declining NTD burdens, leading to resurgence and increased mortality among vulnerable populations worldwide, with devastating consequences for millions of people throughout the world. Conclusions This review examines the role of countries and organizations in fighting tropical diseases, with a perspective on the potential consequences of the U.S. exit from the WHO. We also discuss the importance of cross-border collaborations in fighting tropical diseases, healthcare systems strengthening efforts, and a call to strengthen efforts through other sources of funding and collaborations.